A Pd/C‐CeO2 Anode Catalyst for High‐Performance Platinum‐Free Anion Exchange Membrane Fuel Cells. (8th April 2016) - Miller, Hamish A.; Lavacchi, Alessandro; Vizza, Francesco; Marelli, Marcello; Di Benedetto, Francesco; D'Acapito, Francesco; Paska, Yair; Page, Miles; Dekel, Dario R.
Abstract: One of the biggest obstacles to the dissemination of fuel cells is their cost, a large part of which is due to platinum (Pt) electrocatalysts. Complete removal of Pt is a difficult if not impossible task for proton exchange membrane fuel cells (PEM‐FCs). The anion exchange membrane fuel cell (AEM‐FC) has long been proposed as a solution as non‐Pt metals may be employed. Despite this, few examples of Pt‐free AEM‐FCs have been demonstrated with modest power output. The main obstacle preventing the realization of a high power density Pt‐free AEM‐FC is sluggish hydrogen oxidation (HOR) kinetics of the anode catalyst. Here we describe a Pt‐free AEM‐FC that employs a mixed carbon‐CeO2 supported palladium (Pd) anode catalyst that exhibits enhanced kinetics for the HOR. AEM‐FC tests run on dry H2 and pure air show peak power densities of more than 500 mW cm −2 . Abstract : Kostengünstige Zelle : Eine platinfreie alkalische Membran‐Brennstoffzelle mit einer elektrokatalytischen Pd/C‐CeO2 ‐Anode erzeugt Spitzenleistungsdichten von über 500 mW cm −2 . Die morphologische Analyse offenbart eine feine Verteilung der Pd‐Nanopartikel überwiegend auf dem CeO2 ‐Teil des Katalysators.